The role of parents in adolescent obesity treatment: Results of the TEENS+ randomized clinical pilot trial. Issue 3 (3rd October 2021) - Bean, Melanie K.; LaRose, Jessica Gokee; Raynor, Hollie A.; Adams, Elizabeth L.; Evans, Ronald K.; Farthing, Sarah; Wickham, Edmond P.; Mazzeo, Suzanne E.
Summary: Background: The optimal role for involving parents in adolescent obesity treatment is unknown. Objective: To demonstrate that two parent approaches within adolescent obesity treatment are distinct, as evidenced by differential parent outcomes, and determine the preliminary efficacy of each approach on adolescent weight loss. Methods: Adolescent/parent dyads ( N  = 82; mean adolescent age = 13.7 ± 1.2 years) participated in TEENS+, a 4‐month behavioural weight loss treatment. Participants were randomized to: (1) TEENS+parents as coaches (PAC; parent skills training), or (2) TEENS+parent weight loss (PWL; adult behavioural weight loss). Assessments occurred at 0, 4 (post‐treatment), and 7‐months. Within‐ and between‐group repeated measures general linear mixed models examined change in parent weight (∆kg; primary outcome); parenting, feeding, weight control strategies, home environment, and adolescent body mass index (∆BMI; secondary outcomes). Results: PWL parents had greater 4‐month weight losses (∆kg0–4m  = −5.14 ± 4.87 kg) compared to PAC (−2.07 ± 3.89 kg; between‐group p  < 0.01). Key constructs differed between groups as expected. Both groups yielded significant within‐group adolescent ∆BMI0–4m (PWL: −0.97 ± 1.38 kg/m 2 vs. PAC: −0.93 ± 1.42 kg/m 2 ; p s < 0.01); during maintenance, adolescents in PWL had ∆BMI4–7m increases (+0.41 ± 1.07 kg/m 2 ; p  = 0.02) while PAC did not (+0.05 ± 1.31 kg/m 2 ; p  = 0.82). Conclusion: Parent treatments were distinct in implementation and both yielded significant 4‐month adolescent weight loss. Differential weight patterns were observed during maintenance, favouring PAC, warranting further exploration.